2006
DOI: 10.1159/000092683
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Targeting of the Ventrointermediate Nucleus of the Thalamus by Direct Visualization with High-Field MRI

Abstract: Objective: To evaluate the ability of high-field MRI to consistently produce high-resolution, anatomical images of the thalamic ventrointermediate nucleus (Vim) suitable for stereotactic targeting. Methods: MR images of the thalamus of patients treated for essential tremor were acquired prior to treatment using a 3-tesla MR system. Similar images were acquired in 6 volunteers using, for comparison, both a 1.5-tesla and a 3.0-tesla system. Results: The thalamic Vim was clearly and consistently delineated on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 31 publications
4
31
0
Order By: Relevance
“…Following our preliminary results such structures could be the InL or especially the fiber tracks FF/PLR. This hypothesis would confirm previously published data: parts of the InL have been earlier mentioned for tremor reduction (Hirai and Jones, 1989) and several authors (Spiegelmann et al, 2006; Vassal et al, 2012) have reported that chronic stimulation of PLR works very well. Some authors (Caparros-Lefebvre et al, 1999; Vassal et al, 2012) already suggested that parts of the VO or of the zona incerta (Fytagoridis et al, 2012) could be appropriate targets as well.…”
Section: Discussionsupporting
confidence: 92%
“…Following our preliminary results such structures could be the InL or especially the fiber tracks FF/PLR. This hypothesis would confirm previously published data: parts of the InL have been earlier mentioned for tremor reduction (Hirai and Jones, 1989) and several authors (Spiegelmann et al, 2006; Vassal et al, 2012) have reported that chronic stimulation of PLR works very well. Some authors (Caparros-Lefebvre et al, 1999; Vassal et al, 2012) already suggested that parts of the VO or of the zona incerta (Fytagoridis et al, 2012) could be appropriate targets as well.…”
Section: Discussionsupporting
confidence: 92%
“…The ventral intermediate nucleus (VIM) is commonly targeted with deep brain stimulation (DBS) for the treatment of essential tremor ( Figure 2C). The VIM is located laterally within the thalamus and is situated between the ventral lateral (VL) and the ventral posteromedial (VPM) nuclei 1 . Figure 1 3 Tesla axial T2 MR image of a healthy subject shows the head of the caudate (C) and putamen (P), which together make up the striatum.…”
Section: Thalamusmentioning
confidence: 99%
“…Recent advances in imaging technology have enabled the direct anatomical localization of Vim, such as 3-T MRI (Spiegelmann et al 2006 ), diffusion tensor imaging (Ziyan et al 2006 ;Yamada et al 2010 ), and 1.5-T white matter-attenuated inversion recovery (Vassal et al 2012 ) although these technologies…”
Section: Surgical Procedures Of Vim-dbsmentioning
confidence: 99%